The Emirati Sha‘bī House: On Transformations, Adaptation and Modernist Imaginaries - Yasser Elsheshtawy (Arabian Humanities)
In the United Arab Emirates, the Sha‘bī houses — a public housing initiative— offer a counter narrative that stands in opposition to the official vision of a modern and progressive society, exclusively expressed through a spectacular architecture.1 In their adoption of an incremental approach to housing design and the resultant informal architectural language an alternative urban imaginary is ascertained. One in which residents take matters in their own hand and in many ways reject the state’s model. This can also be construed as part of a broader strategy initiated by city residents in various urban settings.2 Within the highly restrictive context of the Gulf such moves can be construed as a form of adaptation and to some extent resistance; an attempt to establish rootedness within a transient and rapidly changing society.